2019
DOI: 10.1002/cbin.11189
|View full text |Cite|
|
Sign up to set email alerts
|

TCF19 contributes to cell proliferation of non‐small cell lung cancer by inhibiting FOXO1

Abstract: Transcription factor 19 (TCF19) harbors a forkhead association (FHA) domain, a proline-rich region, a PHD or RING finger region, suggesting that TCF19 possesses a powerful function. However, its expression and function remains unknown in non-small-cell lung cancer (NSCLC). The function cluster analysis was carried out using Metascape website. 3-(4,5-Dimethyl-2-thiazolyl)2,5-diphenyl-2H-tetrazolium bromide (MTT), colony formation, and anchorage-independent growth ability assay were carried out to detect the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Several studies have reported that TCF19 played an oncogenic role in cancers. [22][23][24] Herein, we also demonstrated that TCF19 promoted cell proliferation in liver cancer by MTT assay and colony formation assay ( Figure 6A-C), which was consistent with the demonstrations in the previous report. 22 However, whether TCF19 also affected the migration and invasion abilities of liver cancer cells was unreported.…”
Section: Tcf19 Promoted the Proliferation And Metastasis Of Liver Cansupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies have reported that TCF19 played an oncogenic role in cancers. [22][23][24] Herein, we also demonstrated that TCF19 promoted cell proliferation in liver cancer by MTT assay and colony formation assay ( Figure 6A-C), which was consistent with the demonstrations in the previous report. 22 However, whether TCF19 also affected the migration and invasion abilities of liver cancer cells was unreported.…”
Section: Tcf19 Promoted the Proliferation And Metastasis Of Liver Cansupporting
confidence: 91%
“…[19][20][21]35,36 However, a lncRNA PVT1-induced microRNA, miR-1207-5p, has been reported to promote growth by directly suppressing STAT6 in breast cancer cells. 37 Subsequently, we demonstrated that miR-1207-5p directly inhibited the expression of TCF19, a newly identified target of miR-1207-5p, that could play an oncogenic role in several cancers, such as colorectal cancer, 23 non-small cell lung cancer, 24 and liver cancer. 22,38 Consistent with the findings of previous studies, 22,38 we demonstrated that TCF19 promoted cell proliferation in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…1a). TCF19 encodes for a transcription factor TCF19 that has been shown to regulate activation of T cells 21 and also involved in cell proliferation 22,23 . A noteworthy example of a highly cell-specific severe COVID-19-risk eGene in regulatory T cells (TREG) was PDE4A (Extended Data Fig.…”
Section: Mainmentioning
confidence: 99%
“…There were no reports of the expression level of THBD in brain tumors, our study showed that THBD was highly expressed in GBM patients, and patients with different expression levels had inequable prognosis. Finally, several studies had found that in non-small cell lung cancer, hepatocellular carcinoma, and colorectal cancer TCF19 (transcription factor 19) could promote cell proliferation and increase tumor invasiveness through some pathways, but there were no reports about its role in GBM [33][34][35][36]. Our study found that TCF19 was highly expressed in GBM patients, and patients with different expression levels also had inequable prognosis.…”
Section: Discussionmentioning
confidence: 54%